The place of individual rights in communal Africa - Samuel Aloysius Ekanem (International Journal of Humanities and Innovation (IJHI), 2020)
This paper has as its objectives the determination of whether traditional African societies were truly communalistic and whether individuals’ rights were subsumed under the community as so many people claimed. This research which was corroborated by other scholars and supported by the body of maxims that guided traditional African societies reveals that traditional African societies were truly communalistic but does not consume individual rights. Individual rights and values existed side by side the communal values and only gave way to communal values in cases of a conflict between the two. The paper recommends that communal values should be made the bedrock of our current democracy to quicken it and make it thrive.